IDENTIFIKASI KEANEKARAGAMAN JENIS FAUNA DI GUA GARUNGGANG - Setiawan, Asep; Supriono, Bambang; Iskandar, Sofian (Universitas Nusa Bangsa, 2018)
The objective of this research is to get Index of species diversity and habitat habitat characteristic in Garunggang Cave in July 2017. The method used is the method of moving observation and time search. A total of 302 individuals consisting of 5 groups of taxa found in Cave of Garunggang (entrance 3). Species diversity in Cave of Garunggang in relatively medium condition (1 <H '<3) with value of diversity index (H') 1,9 based on variable of diversity type using Shannon-Wiener index. Based on its dominance there are 6 faunas that dominate, namely Hipposideros galeritus, Karstarma jacobsoni, Rhaphidophora Sp, Stygophrynus dammermani, Long leg spiders, and Small spiders. The fauna inside the Cave of Garunggang has a unique habitat such as on the floor, walls and roof of the cave. Cave Garunggang is a horizontal cave with a cave mouth circumference of about 3.7 meters and aisle length about 209 meters. This cave is karst cave (limestone). The diameter of the alley of the cave varies with underground rivers with stone and soil substrate and clear watery. The hallway inside the cave is branched off with several ornaments. In the rainy season the aisles become full of water and become a large underground river, evidenced by the presence of litter on the walls and roof of the cave that was carried by the water during the rainy season. The habitat characteristic of the exokarst Cave of Garunggang is known that the Cave of Garunggang has four zones within it, ie bright zone (cave mouth), transition zone, dark zone and total dark zone. At the bright zone (cave mouth) the temperature ranges from 31.8 ° C - 29.9 ° C, the humidity (Rh) ranges from 67.7% - 76.2% and the light intensity ranges from 475.3 - 848 Lux. At the temperature transition zone ranging from 30.4 ° C - 32.2 ° C, the humidity (Rh) ranges from 72.8% - 77.7%, the light intensity shows 0 Lux and the pH indicator shows the number 7 (normal water). In the dark zone the temperature ranges from 31.4 ° C - 30.4 ° C, the humidity (Rh) ranges from 77.1% - 79.1%, the light intensity shows 0 Lux and the pH indicator shows the number 6 (normal water). The final zone is a total dark zone with temperatures ranging from 30.1 ° C - 30.8 ° C, the humidity (Rh) ranges from 79.7% - 79.2%, the light intensity shows 0 Lux, and the pH indicator shows the number 6 (normal water).